Evidence for an adaptation in ROS scavenging systems in human testicular peritubular cells from infertility patients - Kampfer, C. (2012)
Fibrosis, increased amounts of immune cells and expression of COX-2 in the testes of infertility patients provide circumstantial evidence for a specific testicular milieu, in which reactive oxygen species (ROS) could be increased. If ROS level increase and/or ROS scavengers decrease, the resulting testicular oxidative stress may contribute to human male infertility. Primary peritubular cells of the human testis, from men with normal spermatogenesis (HTPCs) and infertile patients (HTPC-Fs), previously allowed us to identify an end product of COX-2 action, a prostaglandin derivative (15dPGJ2), which acts via ROS to alter the phenotype of peritubular cells, at least in vitro. Using testicular biopsies we now found 15dPGJ2 in patients and hence we started exploring the ROS scavenger systems of the human testis. This system includes catalase, DJ-1, peroxiredoxin 1, SOD 1 and 2, glutathione-S-transferase and HMOX-1, which were identified by RT-PCR/sequencing in HTPCs and HTPC-Fs and whole testes. Catalase, DJ-1, peroxiredoxin 1 and SOD 2 were also detected by Western blots and in part by immunohistochemistry in testicular samples. Western blots of cultured cells further revealed that catalase levels, but not peroxiredoxin 1, SOD 2 or DJ-1 levels, are significantly higher in HTPC-Fs than in HTPCs. This particular difference is correlated with the improved ability of HTPC-Fs to handle ROS, which became evident when cells were exposed to 100 μm H2O2. H2O2 induced stronger responses in HTPCs than in HTPC-Fs, which correlates with the lower level of the H2O2-degrading defence enzyme catalase in HTPCs. The results provide evidence for an adaptation to elevated ROS levels, which must have occurred in vivo and which persist in vitro in HTPC-Fs. Thus, in infertile men with impaired spermatogenesis elevated ROS levels likely exist, at least in the tubular wall.